The problem of norovirus infection in animals (literature review) - V. А. Mischenko; A. V. Mischenko; T. B. Nikeshina; O. N. Petrova; Yu. V. Brovko; A. I. Kushlubaeva (Ветеринария сегодня)
Livestock industry efficiency strongly depends on the livability of young animals, mainly during the early postnatal period. Infectious gastroenteritis of newborns manifested as diarrhea occupies the leading place among the diseases of young animals and brings the production and economic losses. The cause of numerous gastrointestinal disorders are physiological, hygienic, infectious and other factors. This pathology is reported in 50–80% of newborn calves, while 15–55% of diseased animals die. The investigations of the etiology of numerous diarrhea cases revealed rota-, corona-, parvo-, enteroviruses and bovine viral diarrhea virus in fecal samples from calves. Inactivated vaccines have been developed in the Russian Federation to prevent viral diarrhea in cattle. Despite their high antigenicity and field effectiveness, numerous cases of diarrhea in newborn calves have been reported in a number of large livestock farms. In fecal samples collected from diseased individuals, noroviruses along with the above-mentioned viruses were detected by electron microscopy. The noroviruses were detected in fecal samples from humans, cattle, pigs, sheep, dogs, cats, mice, as well as in pork and milk samples. The norovirus genome is prone to mutations, resulting in antigenic shifts and recombination, as well as the emergence and rapid spread of new epidemic and epizootic variants. Epidemiological features of norovirus infection include: prolonged shedding of the virus by the diseased animals and carriers, various transmission routes (fecal-oral, contact) and high contagiousness. In late 20th and early 21st century a large number of dairy and meat cattle were imported to the Russian Federation from various countries, including norovirus-infected countries. All this suggests the need to take noroviruses and other viruses (neboviruses, toroviruses, astroviruses, kobuviruses) into account when investigating the etiology of numerous diarrhea cases in newborn calves and necessitates the development of norovirus diagnostic tools and methods, as well as control measures.